SCIENTIFIC AND PRACTICAL SEMINAR “EUROPEAM COUNCIL OF REFORMS” - Кресін, О. В. (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2012)
The substantial reforms taking place in the Council of Europe and the European Court of Human Rights are directly related to the development of the legal system of our state, they can not be ignored; they require a detailed analysis and formation of a certain position of the state, society, science, and changes in approaches to work with these structures. The discussion of these issues was devoted to the scientific and practical seminar "Council of Europe: the problems of reformation", held at the Institute of State and Law of them. VM Koretsky NAS of Ukraine December 13, 2012.